Pengaruh Persepsi Kegunaan, Kemudahan Penggunaan, dan Biaya dalam Pemasaran Media Sosial terhadap Dampaknya pada UMKM di Indonesia - Hasbiah, Sitti (CV. Ulil Albab Corp, 2024)
This study aims to analyze the influence of perceived usefulness, ease of use, and cost efficiency on the adoption of social media marketing and its impact on business performance in Indonesia. Using the technology acceptance model as a theoretical basis, this study involved 72 respondents who were micro, small, and medium business actors who used social media in their marketing activities. Data were collected through an online questionnaire and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results showed that perceived usefulness, ease of use, and cost efficiency significantly influenced the adoption of social media marketing. Social media marketing has been shown to have a very large impact on improving business performance, including in terms of increasing customers, employee creativity, sales, and customer relationships. The managerial implications of this study emphasize the importance of employee training in using social media to improve business performance. This study also provides recommendations for further research, including the addition of new variables, the influence of cultural differences, and increasing the number of respondents to strengthen the validity and reliability of the results.